CRISPR/Cas9- and Cas3-mediated modification of copy number variation in rice - Park, Hyungjun; Kuroha, Takeshi; Saika, Hiroaki; Kuroda, Masaharu; Yoshida, Hitoshi (Frontiers in Genome Editing, 2025)
IntroductionCopy number variation (CNV) is one of the crucial elements among genomic structural variations that span plant breeding. However, its impact on agricultural traits has remained elusive.MethodsWe modulated CNVs using two genome-editing technologies, CRISPR/Cas9 and Cas3, along with their verification methods in rice to elucidate the effect of CNVs and further harness to improve relevant agronomic traits.ResultsThe addition of cytosine extension to the conventional single-guide RNA and its combination with Cas9 generated a frameshift mutation in parts of the OsGA20ox1 gene copies, substantially modifying its CNV. Phenotypes of the copy number variants revealed OsGA20ox1 copy number as a determinant of seedling vigor in rice. The Cas3 nuclease, which induces large-scale deletions, effectively decreased the copy number of the OsMTD1 gene. We verified the copy number of each gene by combining droplet digital polymerase chain reaction (ddPCR), Sanger sequencing, and bioinformatics tools.DiscussionAltogether, the two technologies are expected to lay the foundation for new approaches to plant breeding by controlling CNV.